Comparison of penile measurements between Nepalese boys with and without hypospadias (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Comparison of penile measurements between boys with and without hypospadias is important to determine whether there is any truth in the notion that the hypospadic penis is shorter than its age-matched normal counterpart. This study was designed to check whether there was any difference in penile sizes between Nepalese boys with and without hypospadias.Methods: A cross-sectional study was conducted among 72 Nepalese boys (36 with hypospadias and 36 without hypospadias) attending the paediatric surgical unit of Kathmandu Medical College Teaching Hospital between July 2019 and June 2020. The penile length was measured in both the flaccid state and the stretched state yielding the flaccid penile length (FPL) and the stretched penile length (SPL) for each subject utilizing standardized measuring conditions. The SPL/FPL ratio was calculated for each patient.Results: The mean FPL in the hypospadias group (A) was 3.42±0.80cms while that in the normal group (B) was 3.62±0.61cms. The mean SPL in group A was 4.58±0.94cms compared to 5.52±0.68cms in group B. The SPL/FPL ratio was 1.34±0.14 in group A compared to 1.54±0.17 in group B. The difference in FPL was not significant between groups but the difference in SPL and the SPL/FPL ratio was statistically significant between groups.Conclusion: The flaccid penile length (FPL) does not vary between the two groups. However, the stretched penile length (SPL) and the Stretched penile to Flaccid penile length ratio (SPL/FPL ratio) are significantly different between the two groups of boys.